Editorial [Hot Topic: Management of Diabetes Mellitus: The Five Pillars of Wisdom (Guest Editors: C.D.A. Stehouwer, N.C. Schaper and M. Huijberts)] - A. Stehouwer, C. D.; Schaper, N. C.; Huijberts, M. (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2007)
Management of diabetes is a rapidly expanding area. A few decades ago diabetes therapy mainly consisted of diet, sulfonylurea derivatives in type 2 and insulin in type 1 diabetes. However, at the same time exciting new concepts were discovered involving the interactions between lipid and glucose metabolism, on the biochemical and haemodynamic pathways involved in the development of vascular complications, etc. But the gap between science and practise was too large. This issue of CMC-IEMA is dedicated to new insights in the pathophysiology and treatment of diabetes and its complications. These articles clearly show that science is reaching practise. Diabetes therapy is currently based on 5 pillars: stimulation of self-management, restoration of the metabolic imbalances associated with the diabetic state, aggressive treatment of cardiovascular risk factors, measures to prevent microvascular disease and treatment of diabetic complications. The development of hyperglycaemia in type 2 diabetes is currently seen as the consequence of interplay of several cell types and four major players seem to be involved: adipose tissue, liver, muscle and pancreas. In summary, during fasting insulin levels are low and the liver is responsible for maintaining blood glucose levels at a sufficient level to enable survival. During fasting, free fatty acids (FFAs), derived from the breakdown of fat in adipose tissue, are converted to glucose by the liver. After a meal there is an influx of nutrients, and glucose levels rise which is accompanied by a rapid increase in insulin secretion by the pancreas. The elevated insulin levels inhibit glucose production by the liver and release of FFAs by adipose tissue; moreover insulin stimulates the uptake of glucose by insulin sensitive tissues such as muscle, liver and adipose tissue. In addition, insulin facilitates the uptake of FFAs. In type 2 diabetes these finely tuned processes are clearly deranged. Muscle, liver and fat cells are less sensitive to insulin, resulting in enhanced glucose and FFA production by the liver and fat cells, respectively. After a meal, nutrients are cleared more slowly due the combination of insulin resistance and impaired insulin secretion by the pancreas. As discussed by Hesselink et al, the close interaction between fat and muscle cells could help to explain the development of insulin resistance (Ref Hesselink). Overflow of fat from adipose tissue to muscle could be one of the important mechanisms in the development of insulin resistance in obesity, “lipotoxicity”. Recent studies indicate that intramyocellular accumulation of fat results in mitochondrial dysfunction with impaired fatty acid oxidation and impaired insulin signalling as a consequence. A drastic reduction in nutrient intake, as discussed by Nijhuis et al, results in a rapid improvement in insulin sensitivity in obese type 2 diabetic patients and bariatric surgery can be a very effective treatment in morbid obese type diabetic patients (Ref Nijhuis). Blaak describes in her article the relationship between dietary fat, FFAs and insulin resistance (Ref Blaak). These insights could be the basis for new dietary interventions in which not the absolute amount of fat intake is changed to reduce caloric intake but in which the type of fat intake is modulated to improve insulin sensitivity. In the article of Van Loon another dietary strategy is explored (Ref van Loon). Specific amino acids/ proteins have been shown in short term experiments to stimulate insulin secretion and to reduce muscle proteolysis and/or to stimulate protein synthesis, which could have beneficial effects on insulin sensitivity. Supplementation with specific amino acids/ proteins in combination with an exercise programme seems therefore an attractive intervention for sedentary type 2 diabetic patients, which remains to be tested. Insulin secretion is not only influenced by nutrients but also by several gut hormones (incretins) and several lines of evidence suggest that one of these incretins, glucagon like peptide-1 (GLP-1), could be an attractive new therapeutic modality (Ref Holst). As discussed by Holst GLP-1 has several pancreatic and extra-pancreatic actions, which might be beneficial for patients with type 2 diabetes. Aggressive treatment of hyperglycaemia is one of the cornerstones in the prevention of diabetic complications. Unfortunately, most patients do not succeed in maintaining a normal glucose level day after day. As described by Schalkwijk, this chronic hyperglycaemia results in the formation of advanced glycation end products (AGEs), which could be one of the pivotal steps in the development of diabetic micro- and macroangiopathy (Ref Schalkwijk).......